Effects of the skp1 gene of the SCF complex on lipid metabolism and response to abiotic stress in Chlamydomonas reinhardtii - Deng, Xiao Dong; Wang, Meng; Liu, Si Hang; Xu, Dian Long; Fei, Xiao Wen (Frontiers in Plant Science, 2025)
SKP1 (S-phase kinase-associated protein 1) is a key member of the SCF (SKP1-Cullin1-F-box) E3 ligase complex. The SCF complex is involved in regulating various levels of plant physiology, including regulation of cellular signaling and response to abiotic stresses. While the function of SKP1 in plants is well known, its function in algae remains poorly understood. In this study, we investigated the role of the Chlamydomonas reinhardtii skp1 gene using RNAi interference and overexpression approaches. Subcellular localization of SKP1 was performed by transient expression in onion epidermal cells. For abiotic stress assays, the growth of skp1 RNAi and overexpression recombinant strains was examined under conditions of high osmolality (sorbitol), high salinity (NaCl) and high temperature (37°C). Our results showed that skp1 silencing significantly reduced oil accumulation by 38%, whereas skp1 overexpressing led to a 37% increase in oil content, suggesting that skp1 plays a crucial role in regulating oil synthesis and may influence lipid accumulation by regulating photosynthetic carbon flux partitioning. Subcellular localization analysis revealed that skp1 was predominantly localized within the nucleus. Furthermore, our results showed that SKP1 responds to abiotic stresses. Under sorbol and NaCl stress conditions, RNAi interference strains exhibited better growth than controls; however, their growth was comparatively impaired under 37°C stress compared to controls. On the other hand, overexpression strains showed weaker growth under sorbol and NaCl stress but were more tolerant to 37°C heat stress. These results illustrate the functional diversity of SKP1 in Chlamydomonas. This study provides an important complement for lipid metabolism and abiotic stress regulation in microalgae.